Potato Peels Waste Extract as Natural Antioxidant and Antimicrobial in Lemon Carbonated Soft Drink - Mohamed Mahmoud Helal; Tarek Ahmed El-Adawy; Alaa Ahmed El-Beltagy; Aboelfateh Abdelkader El-Bedawey; Saad Michael Youssef (University of Sultan Ageng Tirtayasa, 2024)
Most soft drinks are generally considered ready media for spoilage microbial growth. Deterioration of these products by undesirable microorganisms can alter the sensory quality of the product which also poses a major public health risk. The soft drink category with lemon made up 85% of all bacterial contamination and was considered microbiologically unsafe due to a lack of preservatives. Over the last decade the world has been generating a high quantity of potato peel waste. These peels have several economic benefits but there is mismanagement or inappropriate valorization that could present risks to environment and public health. Potato peels waste contain several bioactive components. These components are known to provide human health benefits including antioxidant and antimicrobial properties. The use of potato peels as natural antimicrobial compounds are believed to play important role in reduce or inhibit microbial growth in food stuff. Results confirmed that the antimicrobial action of potato peel methanol extract (PPME) at 200 ppm concentration, was higher and achievable than using weak-acid preservatives (citric acid), where total bacterial count, aciduric bacteria, yeast and mold viable counts of standard lemon product (without PPME) showed tolerance to low pH and was associate to spoilage the final product even using citric acid. Otherwise, both standard and PPME lemon soft drink formulations were free of pathogenic bacteria (Coliform & E.coli) after production and during 6 months storage period. All quality sensory attributes gradually decreased (P ≤ 0.05) up to the sixth month of storage. After production, taste, appearance and overall acceptability of PPME- lemon soft drink formulation had lower (P ≤ 0.05) values than standard lemon soft drink formulation (control). In contrast, PPME-lemon soft drink formulation had higher (P ≤ 0.05) quality sensory values than standard lemon soft drink formulation (control) as affected by PPME addition.